Chironomid-Based Modern Summer Temperature Data Set and Inference Model for the Northwest European Part of Russia - Larisa Nazarova; Liudmila Syrykh; Ivan Grekov; Tatiana Sapelko; Andrey B. Krasheninnikov; Nadia Solovieva (Water, 2023)
Northwestern Russia remains the only region in Northern Eurasia where no regional chironomid-based inference model for quantitative palaeoclimatic reconstructions has been developed. Using palaeolimnological methods, we investigated the subfossil chironomid remains in surface sediments from a data set of 98 lakes from nine subregions of the European part of Northern Russia. We identified 143 chironomid taxa in the investigated lakes. Multivariate statistical analyses of chironomid and environmental data demonstrated that the mean July air temperature (T July), distance from the tree line, water depth, pH, and altitude explain the most significant variance in chironomid distribution. T July appeared to be the most important environmental variable. We established a chironomid-based inference model for reconstructing T July from subfossil data. The resulting West Russian two-component WA-PLS model includes 96 lakes (two lakes were excluded as outliers), 143 chironomid taxa, r2 = 0.84 (r2 boot = 0.60), RMSEP boot = 1.34 °C, and can be recommended for application in palaeoclimatic studies in the East of Northern Eurasia.